1972
DOI: 10.1172/jci107021
|View full text |Cite
|
Sign up to set email alerts
|

Human prolactin and thyrotropin concentrations in the serums of normal and hypopituitary children before and after the administration of synthetic thyrotropin-releasing hormone

Abstract: A B S T R A C T Synthetic thyrotropin-releasing hormone (TRH) was administered to normal children and hypopituitary patients in a dose of 7 jg/kg i.v. over 30-60 sec. Serum thyrotropin (TSH) and prolactin (HPr) concentrations were measured by radioimmunoassay before and at 15-min intervals for 2 hr after TRH. In 20 normal children HPr rose from a mean baseline value of 7.0±1.2 (SEM) ng/ml to a mean peak value of 39.5±5 ng/ml.In 11 patients with growth hormone (GH) deficiency without TSH deficiency, HPr values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
1
3

Year Published

1973
1973
1990
1990

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 17 publications
1
20
1
3
Order By: Relevance
“…Gynecomastia is a common finding among pubertal boys; usually, it is limited to a nodule of subareolar tissue, and ordinarily the breast enlargement begins during the early stages of the pubertal process and thereafter regresses within [6][7][8][9][10][11][12][13][14][15][16][17][18] mo. Levels of plasma testosterone (T),' estradiol-17# (E2), serum luteinizing hormone (LH), and follicle-stimulating hormone (FSH) in boys with pubertal gynecomastia are not significantly different from those in unaffected boys (1), although a relative increase in the level of plasma E2 compared with that of T during certain times of the day has been found (2).…”
Section: Introductionmentioning
confidence: 99%
“…Gynecomastia is a common finding among pubertal boys; usually, it is limited to a nodule of subareolar tissue, and ordinarily the breast enlargement begins during the early stages of the pubertal process and thereafter regresses within [6][7][8][9][10][11][12][13][14][15][16][17][18] mo. Levels of plasma testosterone (T),' estradiol-17# (E2), serum luteinizing hormone (LH), and follicle-stimulating hormone (FSH) in boys with pubertal gynecomastia are not significantly different from those in unaffected boys (1), although a relative increase in the level of plasma E2 compared with that of T during certain times of the day has been found (2).…”
Section: Introductionmentioning
confidence: 99%
“…Two examples of these alterations are the increased PRL response to TRH (1,2) and the stimulation of GH secretion by TRH in hypothyroid children (3) and adults (4); these responses do not occur in normal subjects (5). It has been shown that many children suffering from congenital hypothyroidism manifest high serum TSH concentrations for prolonged periods despite adequate replacement therapy, clinical euthyrodism, and normal serum levels of thyroid hormones (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…There is, however, relatively little information on the PRL response to TRH in children (Foley et al 1972;Kaplan et al 1972;Okada et al 1978 ;Suter et al 1978 ;Roitman et al 1980;Abe et al 1982Abe et al , 1983). Since it has been known that PRL plays some role for breast development (Frantz 1981) …”
mentioning
confidence: 99%